2015
DOI: 10.1016/j.cgh.2015.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Levels of Adipokines and Insulin With Risk of Barrett's Esophagus: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND & AIMS Metabolically active visceral fat may be associated with esophageal inflammation, metaplasia, and neoplasia. We performed a meta-analysis to evaluate the association of serum adipokines and insulin with Barrett's esophagus (BE). METHODS We performed a systematic search of multiple electronic databases, through April 2015, to identify all studies reporting associations between leptin, adiponectin, insulin, insulin resistance, and risk of BE in adults. Comparing the highest study-specific cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 49 publications
1
24
0
1
Order By: Relevance
“…Adipokines such as adiponectin and leptin may influence the association between visceral obesity and BE. High levels of leptin are associated with a two-fold increased risk of BE 27 where as adiponectin seems to have a protective effect atleast in some studies 28 . Leptin levels are known to be higher in women than in men after adjusting for total body fat 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Adipokines such as adiponectin and leptin may influence the association between visceral obesity and BE. High levels of leptin are associated with a two-fold increased risk of BE 27 where as adiponectin seems to have a protective effect atleast in some studies 28 . Leptin levels are known to be higher in women than in men after adjusting for total body fat 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated an association between levels of different circulating adipokines and BE or EA. 5,21,27-29 It seems unlikely that a single factor is responsible for all of the risk attributable to obesity; rather it would seem that abdominal obesity (if not counteracted by gluteofemoral obesity) results in a milieu of circulating metabolic factors that promote BE and EA. Risk prediction models for BE that include a term for waist-to-hip ratio have been shown to have reasonable discriminatory ability; 30,31 whether gluteofemoral (hip circumference) and abdominal (waist circumference) obesity separately discriminate better between persons with and without BE than waist-to-hip ratio is unknown and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…4 These systemic effects have been associated with non-esophageal cancers and a recent meta-analysis found they may be important in BE. 5 …”
mentioning
confidence: 99%
“…Higher adiponectin levels were independently associated with aberrant healing of esophageal injury in GERD (positive correlation not negative). Parallel to our study, another study by Chandar et al 22 summarized data from nine observational studies (10 independent cohorts; 1432 patients with BE and 3550 controls). When patients with BE were matched to population controls in five studies, subjects within the highest tertile of serum adiponectin level showed decreased odds of BE (odds ratio: 0.65; 95% CI: 0.31-1.36).…”
Section: Discussionmentioning
confidence: 72%
“…Higher adiponectin levels were independently associated with aberrant healing of esophageal injury in GERD (positive correlation not negative). Parallel to our study, another study by Chandar et al 22. summarized data from nine observational studies (10 independent cohorts; 1432 patients with BE and 3550 controls).…”
Section: Discussionmentioning
confidence: 80%